Neurotic Personality Traits and Depression among First Year Medical and Dental Students in Universiti Sains Malaysia - Kelvin, L YS; Othman, Zahiruddin; Othman, A; Yasin, MAM (Malaysian Psychiatric Association, 2013)
Objective: This study aims to evaluate the association of neurotic personality traits and coping styles with depression amongst first year medical and dental students. Methods: A total of 167 students consisting of 133 medical and 34 dental students in their first year were recruited. All the subjects were assessed using BDI, NEO PI-R (N) and Brief COPE for depression, neurotic personality traits and coping styles respectively. Result: First year dental students were 3 times more likely to have depression than first year medical students. Students who scored high and very high on the total Neuroticism factor and the Depression facet of NEO PI-R (N) were 3.6 times and 7 times more likely to have depression than students who scored very low, low or average for the above scales. All coping styles and other socio-demographic factors showed no association with depression. Conclusion: Neurotic personality traits are significantly associated with depression. NEO PI-R (N) proved to be a useful tool to evaluate the neurotic traits among medical and dental students allowing early interventional measures to those who need it